Acceptance by laypersons and medical professionals of the personalized eHealth platform, eHealthMonitor - Griebel, Lena; Kolominsky-Rabas, Peter; Schaller, Sandra; Siudyka, Jakub; Sierpinski, Radoslaw; Papapavlou, Dimitrios; Simeonidou, Aliki; Prokosch, Hans-Ulrich; Sedlmayr, Martin (Informatics For Health & Social Care, 2016)
Often, eHealth services are not accepted because of factors such as eHealth literacy or trust. Within this study, eHealthMonitor was evaluated in three European countries (Germany, Greece, and Poland) by medical professionals and laypersons with respect to numerous acceptance factors.Questionnaires were created on the basis of factors from literature and with the help of scales which have already been validated. A qualitative survey was conducted in Germany, Poland, and Greece.The eHealth literacy of all participants was medium/high. Laypersons mostly agreed that they could easily become skillful with eHealthMonitor and that other people thought that they should use eHealthMonitor. Amongst medical professionals, a large number were afraid that eHealthMonitor could violate their privacy or the privacy of their patients. Overall, the participants thought that eHealthMonitor was a good concept and that they would use it.The main hindrances to the use of eHealthMonitor were found in trust issues including data privacy. In the future, more research on the linkage of all measured factors is needed, for example, to address the question of whether highly educated people tend to mistrust eHealth information more than people with lower levels of education.
EVALuna2:171